(untitled) (The Research of Medical Science Review, 2025)
Background: Morton’s neuroma is a painful condition that affects the ball of foot results in severe pain and causes difficulty in walking. Wearing high heel, center of gravity of body shifts forward, decreases base of support on the weight-bearing foot, metatarsophalangeal joint moves into hyper-extension, and nerve compresses between metatarsal heads, resulting in neuroma. Objectives: The aims and objectives of our study were to evaluate the prevalence of Morton’s neuroma and its association with pain and disability among Sales Girls wearing high heels. Methodology: A cross-sectional study was conducted on sales girls wearing high heels (n=98) from different shopping malls in Faisalabad. A 12 weeks study from February 2024 to June 2024 after approval of synopsis (IRB ref no# TUF/IRB/400/24). A convenient sampling technique was used to collect the sample size. After obtaining informed consent from the participants, screening was done by screening tool. The Thumb Index Finger Squeeze test and a screening tool based on inclusion and exclusion criteria were used to screen the study population. The study comprised sales girls between the ages of 20 and 35 who had worn high heels for at least four hours a week, for at least a year, with a minimum heel height of 5 cm or more, and who were willing to participate. With SPSS version 20, statistical analysis was carried out. Result: The research finding demonstrates 59.18% prevalence of Morton’s neuroma among sales girls wearing high heels with the experience of moderate level associated with pain and disability. Conclusion: It was concluded that prevalence of Morton’s Neuroma among sales girls wearing high heels was high. The findings showed that high heels were significantly associated with the prevalence of Morton’s Neuroma.